Risk determination for the implantation process of software systems - Ortiz, Felipe; Panizzi, Marisa D.; Bertone, Rodolfo Alfredo (2019)
From the analysis of software companies in Argentina, weaknesses in risk management have been observed. This impacts in quality management because risk planning is a requirement specified by all standards. As part of a general study about the implantation of software systems, the aim of this work is to analyze the risks associated to such process. This proposal envisages the activities and tasks of the ISO/IEC 12207 standard transition process. For the assessment of the proposed risks, the ISO/IEC 31010 standard is adopted. Furthermore, associated procedures are suggested to either avoid or mitigate risks. The work was tested in a real environment to determine its viability. The case study consisted of the risk analysis of the implantation of the management system module of a multinational company’s advertising agency. This revealed flaws in the management of the analyzed risks and provided feedback for the study.
Formato de archivo PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
Congreso Argentino de Ciencias de la Computación (25to : 2019 : Río Cuarto, Córdoba)
Keywords: PROCESO DE SOFTWARE; GESTIÓN DE RIESGOS